Concept of British Commonwealth in Activities of Round Table Group at Beginning of ХХ Century - A. V. Sagimbaev (Tsentr nauchnykh i obrazovatelnykh proektov, 2021)
Some aspects of the complex intellectual discussion that accompanied the transformation of the British colonial system at the beginning of the 20th century are considered. Based on the analysis of published works, a generalized description of the conceptual views of the members of the “Round Table” group regarding the formation of the political and legal foundations of the British Commonwealth, as well as the development of close cooperation between Great Britain and self-governing dominions is given. At the same time, special attention is paid to the study of the practical significance of the ideas of A. Milner, L. Curtis and other intellectuals who were part of the group of intellectuals for transforming the forms and methods of managing the vast domains of the British crown. This transformation was due to a complex of factors of a socio-economic, political, moral and psychological nature, which Great Britain was forced to face in the first decades of the 20th century. It is noted that the changes that took place in the governing system of the largest colonial empire in history, among other things, contributed to the subsequent formation of mechanisms of international influence, which at the beginning of the 21st century were called “soft power”. It is shown that, on the other hand, in their theoretical constructions A. Milner and his followers strove to preserve the continuity of the ideology of imperialism, which gained popularity in the British establishment in the late Victorian period.